2017
DOI: 10.1080/19338244.2017.1322934
|View full text |Cite
|
Sign up to set email alerts
|

Risk due to exposure to metallic elements in a birdshot factory

Abstract: The contribution of biological and environmental monitoring to the risk assessment of occupational exposure to lead (Pb), arsenic (As), and antimony (Sb) was studied in 18 workers at a birdshot factory (Exposed) and in 18 control workers (Controls) by the determination of both airborne Pb (PbA) and airborne As (AsA) only in the exposed workers and blood Pb (PbB), erythrocytic zinc protoporphyrin (ZPP), urinary Sb (SbU), and the urinary As species in exposed workers and controls. PbA (12-42 μg/m) and AsA (1-4 μ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…It is hypothesized that Cd reaches the prostate by mimicking certain hormones, but more studies are required [40]. Studies have found a correlation between air cadmium and blood cadmium and DNA damage [41,42], further suggesting the importance of air cadmium. Most of the literature addresses the biological effect of cadmium on the initiation and promotion of PC, with little attention to progression (an increase in genomic instability, tumor growth and metastasis) of already established malignancy.…”
Section: Discussionmentioning
confidence: 99%
“…It is hypothesized that Cd reaches the prostate by mimicking certain hormones, but more studies are required [40]. Studies have found a correlation between air cadmium and blood cadmium and DNA damage [41,42], further suggesting the importance of air cadmium. Most of the literature addresses the biological effect of cadmium on the initiation and promotion of PC, with little attention to progression (an increase in genomic instability, tumor growth and metastasis) of already established malignancy.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to Vitamin B 12 and folate, the kidney also metabolizes Hc; elevated blood levels of Hc have been found in patients with kidney disease [80,81]. Although the pathogenesis of hHc in renal disease is still unknown, both in vivo and in vitro studies have suggested that the kidney plays a fundamental role in Hc metabolism [81,82]. Data from previous studies show that high blood Hc values in patients with renal disease are related to the reduction of Hc clearance from the body due to metabolic accumulation [83,84].…”
Section: Chromium (Cr)mentioning
confidence: 99%
“…Antimony (Sb) and its compounds are widely used in some industries, including alloy, plastic, glass, and textile industries [ 1 , 2 , 3 , 4 , 5 , 6 ]. The permissible exposure limit (PEL) established by the US Occupational Safety and Health Administration for exposure to antimony and compounds is 0.5 mg/m 3 of antimony in the workplace based on a working 8 h shift and a 40 h week [ 7 ].…”
Section: Introductionmentioning
confidence: 99%